Developments in stiff ground support in deep potash operations at the Vanscoy Mine - Coleman, T.J.; Neely, D.D. (Ground Support 2019: Proceedings of the Ninth International Symposium on Ground Support in Mining and Underground Construction, 2019)
This paper presents a case study of the development of ground support practices at Nutrien’s Vanscoy potash mine, the deepest (>1,100 m) conventional evaporite mine in North America. The majority of the underground excavations at Saskatchewan potash mines are unsupported and rely upon the principle of stress control to manage ground conditions. Adverse ground conditions are typically addressed in three ways: changing mining horizon to avoid disturbed ground, cutting down of bad ground, or installation of ground support. The two former approaches often result in extended interruptions to production whereas installation of ground support allows access to be maintained and production to continue. The timedependant creep properties of the evaporites led to the historical approach of using a soft ground support system to accommodate the large deformations typically seen. The softness of the ground support system at potash operations was typically achieved by utilising point anchored mechanical rockbolts, partial encapsulation of resin rebar bolts, or by introducing a softer element in to a fully encapsulated resin rebar support element, at Vanscoy a wood washer was used. The experience of one of the authors with the improvement of excavation stability following the introduction of stiff resin encapsulated AT rockbolts for secondary ground support at the deep (>1,300 m) Boulby potash mine in the UK led to initial instrumented trials at the Vanscoy Mine. Multipoint magnesonic extensometers were introduced to the mine to provide detailed measurement of back deformation to assess the impact of increasing the ground support stiffness on back behaviour. The magnesonic extensometers comprise of 20 magnetic reference anchors installed over a depth of 7 m allowing precise high resolution measurement of back deformation. The introduction of magnesonic extensometers to monitor the influence of stiffening the ground support system proved invaluable in understanding the mechanism of ground support/rock mass interaction in the immediate stratified back of development and production excavations. The Vanscoy Mine has adopted stiffer ground support practices and continues to explore other ground support technologies in the pursuit of safe optimised ground support practices.